PERBANDINGAN EFISIENSI PENATALAKSANAAN APENDISITIS AKUT PADA PASIEN JAMINAN KESEHATAN NASIONAL DENGAN PASIEN UMUM (STUDI KASUS DI RSUD PANEMBAHAN SENOPATI BANTUL) - Agus Tri Widiyantara; Arlina Dewi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2016)
Background: BPJS PBI’s participants patients that a part of National Health Insurrance have financing with prospective payment system, while general patient use fee for service., To avoid losses, the hospital must manage patients more efficiently in the prospective payment system than the fee for service with strict quality control and control of costs Methods: The type of research is a quantitative research using secondary data. Population is BPJS PBI’s patient and general patients who experiencing uncomplicated acute appendicitis and action appedictomi. There are 60 respondent. Analyses test using independent t test and Mann-Whitney test. Results and Discussion: BPJS PBI’s participants patient’s length of stay are shorter than general patients (p <0.001). The management cost of BPJS PBI participant patients are lower and significantly different than public patients at the component cost of the drugs (p <0.001), the cost of a physician's examination (p = 0.012), the cost of accommodation (p <0.001), the cost of BMHP (p <0.001), supporting examination (p = 0.023) and total cost (p <0.001). There is no differences of operating costs. BPJS PBI’s participants care costs are lower than public patients but there was no significant difference (p = 0.487). Conclusion: Based on the length of stay and cost management in appendicitis procedures, BPJS PBI’s participant patients more efficient than general patients.